The urgency of refining the accounting standards of state tax revenue and receivables - Asqolani; Budi Mulyana (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara)
Indonesia's Central Government Balance Sheet reflects substantial amounts of tax revenue and receivables, indicating the potential for significant state budget receipts. However, for the past 5 years, the audit report of the Audit Board of the Republic of Indonesia (Badan Pemeriksa Keuangan, BPK) on the Central Government Financial Report (LKPP) has consistently identified accuracy issues of tax receivable balances. Accordingly, this study explores the accounting problems related to tax revenue and receivables within the Directorate General of Taxes (DGT) and proposes solutions how to improve them. A qualitative case study approach was employed using data collected through documentation and triangulated interviews with the Ministry of Finance (DGT and Directorate General of Treasury), BPK, and the Government Accounting Standards Committee. Results showed that inadequate regulation on the accrual-based reporting of tax transactions leads to underreported state revenue and receivables. The findings also provide empirical evidence that adopting International Public Sector Accounting Standards (IPSAS) 23, which covers revenues from non-exchange transactions (taxes and transfers), into Indonesia’s Government Accounting Standards could solve tax revenue and receivable accounting problems. Furthermore, a comparative analysis of ASEAN countries revealed that Malaysia, Singapore, and the Philippines have already incorporated IPSAS 23 into their accounting frameworks.